The development of anticancer ruthenium(ii) complexes: from single molecule compounds to nanomaterials - Zeng, Leli; Gupta, Pranav; Chen, Yanglu; Wang, Enju; Ji, Liangnian; Chao, Hui; Chen, Zhe-Sheng (Chemical Society reviews, 2017)
Cancer is rapidly becoming the top killer in the world. Most of the FDA approved anticancer drugs are organic molecules, while metallodrugs are very scarce. The advent of the first metal based therapeutic agent, cisplatin, launched a new era in the application of transition metal complexes for therapeutic design. Due to their unique and versatile biochemical properties, ruthenium-based compounds have emerged as promising anti-cancer agents that serve as alternatives to cisplatin and its derivertives. Ruthenium( iii ) complexes have successfully been used in clinical research and their mechanisms of anticancer action have been reported in large volumes over the past few decades. Ruthenium( ii ) complexes have also attracted significant attention as anticancer candidates; however, only a few of them have been reported comprehensively. In this review, we discuss the development of ruthenium( ii ) complexes as anticancer candidates and biocatalysts, including arene ruthenium complexes, polypyridyl ruthenium complexes, and ruthenium nanomaterial complexes. This review focuses on the likely mechanisms of action of ruthenium( ii )-based anticancer drugs and the relationship between their chemical structures and biological properties. This review also highlights the catalytic activity and the photoinduced activation of ruthenium( ii ) complexes, their targeted delivery, and their activity in nanomaterial systems. This review covers ruthenium( ii ) complexes as anticancer drugs in single molecules and nanomaterials and includes targets, mechanisms, SAR, PDT and nano-systems.